Association of red cell distribution width/albumin ratio and 28-day mortality in chronic obstructive pulmonary disease patients with atrial fibrillation: a medical information mart for intensive care IV study - Jian-min Qu; Xia-hong Tang; Wen-juan Tang; Li-ya Pan (BMC Cardiovascular Disorders)
Abstract Background Chronic obstructive pulmonary disease (COPD) complicated by atrial fibrillation (AF) in ICU patients is associated with higher risks of adverse outcomes. The red cell distribution width to albumin ratio (RAR), may predict mortality in critical illness, yet its link to 28-day mortality in ICU patients with COPD and AF remains unclear. Methods This retrospective cohort study analyzed 693 ICU patients with COPD and AF from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, grouped by RAR tertiles. The primary endpoint was 28-day mortality, with secondary endpoints including 90-day, 365-day, and ICU mortality. Multivariate cox models estimated hazard ratios (HRs) for mortality, while restricted cubic spline regression assessed the linearity of the RAR-mortality relationship. Kaplan-Meier curves compared survival across tertiles, and subgroup analyses explored RAR’s impact across age, gender, race, and comorbidities. Results Our study included 693 ICU patients with both COPD and AF, with an average age of 74.9 years. The 28-day mortality was 30.7%. Patients in the highest RAR tertile had significantly worse 28-day survival (p < 0.0001). Higher RAR was linearly associated with increased 28-day mortality (p for non-linearity > 0.05), with each 1-unit increase in RAR linked to an 18% rise in mortality risk (95% CI: 1.08–1.29). Sensitivity analyses confirmed RAR’s relevance for 90-day, 365-day, and ICU mortality. Conclusions RAR is independently associated with 28-day mortality in COPD patients with AF. Elevated RAR levels correlate with higher 28-day mortality rates in this population. Clinical trial number Not applicable.